VIS-NIR-SWIR spectroscopy in sugarcane (Saccharum officinarum L.) cultivation for phytosanitary purposes - Natália Correr Ré; Carlos Augusto Alves Cardoso Silva; Ana Karla da Silva Oliveira; Matheus Luís Caron; Matheus Sterzo Nilsson; Daniel Garbellini Duft; Peterson Ricardo Fiorio (Ciência Rural)
ABSTRACT: One of the causes of productivity loss in sugarcane cultivation has been associated with the species Diatraea saccharalis, also known as the sugarcane borer. Therefore, this study evaluated the feasibility of using hyperspectral sensors to obtain the leaf spectral response of sugarcane in different periods of infestation at leaf and canopy levels to diagnose D. saccharalis damage in advance. The study included three varieties of sugarcane: CTC9003BT, CTC4, and RB966928. The insecticide Altacor® was used to control pestsin half of the plots. Data collection occurred at the following stages: sprouting, tillering, stalke longation, and early maturation. Data regarding relative water content (RWC), leaf spectral signature in the laboratory and canopy, vegetation indices (NDVI and MCARI), productivity, purity, and total recoverable sugar (TRS) were collected to evaluate the borer effects on the sugarcane crop. The highest RWC was observed for CTC9003BT (60.15%) without insecticide and 59.0% with insecticide. The visible (400-680 nm) and near-infrared (750-1300 nm) spectral bands identified spectral variations in plants with and without sugarcane borer. The percentage of sugarcane borer showed high and negative correlations between productivity, NDVI, and TRS, with coefficients of -0.68, -0.76, and -0.76, respectively. The NDVI and MCARI indices effectively detect plants under stress, but their variation is influenced by multiple factors, making it difficult to associate them with a single problem (sugarcane borer).